Non-mumps Viral Parotitis During the 2014–2015 Influenza Season in the United States. (30th March 2018) - Elbadawi, Lina I; Talley, Pamela; Rolfes, Melissa A; Millman, Alexander J; Reisdorf, Erik; Kramer, Natalie A; Barnes, John R; Blanton, Lenee; Christensen, Jaime; Cole, Stefanie; Danz, Tonya; Dreisig, John J; et al.
Abstract : We investigated a multistate outbreak of acute viral non-mumps parotitis (NMP). Understanding epidemiologic and clinical features of viral NMP might improve diagnostic acumen among clinicians considering illnesses that could be mumps, resulting in more timely treatment and public health action. Abstract: Background: During the 2014–2015 US influenza season, 320 cases of non-mumps parotitis (NMP) among residents of 21 states were reported to the Centers for Disease Control and Prevention (CDC). We conducted an epidemiologic and laboratory investigation to determine viral etiologies and clinical features of NMP during this unusually large occurrence. Methods: NMP was defined as acute parotitis or other salivary gland swelling of >2 days duration in a person with a mumps- negative laboratory result. Using a standardized questionnaire, we collected demographic and clinical information. Buccal samples were tested at the CDC for selected viruses, including mumps, influenza, human parainfluenza viruses (HPIVs) 1–4, adenoviruses, cytomegalovirus, Epstein-Barr virus (EBV), herpes simplex viruses (HSVs) 1 and 2, and human herpes viruses (HHVs) 6A and 6B. Results: Among the 320 patients, 65% were male, median age was 14.5 years (range, 0–90), and 67% reported unilateral parotitis. Commonly reported symptoms included sore throat (55%) and fever (48%). Viruses were detected in 210 (71%) of 294 NMP patients with adequate samples for testing, ≥2 viruses were detected in 37 samples, and 248 total virus detections were made among all samples. These included 156 influenza A(H3N2), 42 HHV6B, 32 EBV, 8 HPIV2, 2 HPIV3, 3 adenovirus, 4 HSV-1, and 1 HSV-2. Influenza A(H3N2), HHV6B, and EBV were the most frequently codetected viruses. Conclusions: Our findings suggest that, in addition to mumps, clinicians should consider respiratory viral (influenza) and herpes viral etiologies for parotitis, particularly among patients without epidemiologic links to mumps cases or outbreaks.